The EU and e-skills - Del Cimmuto, Angelo (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The relevance and strategic nature of digital skills have been recognised and embraced over the past decade both by EU bodies and the political agendas of nation states, and by the organisational logics underlying production processes within companies. The globalisation of economies, the digitalisation of production processes and markets, technology, and the speed of communication flows spread even in the most peripheral geographical areas of the planet and in the most personal spheres of individual life have profoundly changed societies (in terms of policies, relational and interpersonal approaches, culture, habits, clichés) and redesigned the physiognomy not only of advanced countries but also of those that tend to catch up with them.